Reproducibility in Time and Space—The Molecular Weight Effects of Polymeric Materials in Organic Photovoltaic Devices. Issue 5 (7th April 2022) - Gui, Ruohua; Liu, Yang; Chen, Zhihao; Wang, Tong; Chen, Tao; Shi, Rui; Zhang, Kangning; Qin, Wei; Ye, Long; Hao, Xiaotao; Yin, Hang
Abstract: The reproducibility issue is one of the major challenges for the commercialization of large‐area organic electronic devices. It involves both the device‐to‐device variation and opto‐electronic properties in different positions of a single thin film. Herein, the molecular weight effects in polymeric semiconductors with three widely used photovoltaic donor materials P3HT, PBDB‐T, and PM6 are systematically investigated. A simple but effective method is proposed to evaluate the uniformity of large‐area devices by adopting the micron‐level grid electrodes in organic thin films. An interesting phenomenon is observed that the device is gradually improved uniformly with the M w range lower than 100 kg mol −1 . In neat films, both the mobility and energetic disorder values of hole carriers exhibit relatively lower coefficient of variation ( c v ) in high molecular‐weight systems. After blending with the electron‐accepting materials, their bulk heterojunction films also enjoy more uniform hole transfer rates, fluorescence lifetimes, and power conversion efficiencies in single and different devices. This work not only proposes a facile approach to evaluate the electrical properties of large‐area organic thin films, but also demonstrates the relationship between molecular weight and device reproducibility in polymer solar cells. This contribution provides a new insight into the commercial large‐scale production of organic electronics. Abstract : The effects of polymeric molecular weight on reproducibility of charge transport and device performance are systematically investigated. A simple but effective method is proposed to evaluate the uniformity of organic large‐area films. A gradual improvement of reproducibility is observed with polymer molecular weight increasing.